Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
= (12-12) + (11+10) - (9+8) - (7+5) - (4+3) + (2-1)
= 0 + 21 - 17 - 12 - 7 + 1
= 21- 17 - 12 - 7 +1
= 4 - 12 - 7 +1
= -8 - 7 + 1
= -15 + 1
= -14
hết
= 12 - 12 + 11 + ( 10 - 9 ) + ( 8 - 7 ) + ( 5 - 4 ) + 3 + ( 2 -1 )
= 0 + 11 + 1 + 1 + 1 + 3 + 1
= 11 +1 + 1 + 1 + 3 + 1
= 12 + 1 + 1 + 3 + 1
= 13 + 1 + 3 + 1
= 14 + 3 + 1
= 17 + 1
= 18
Đáp án đây nha bạn !!!
Chúc bạn học tốt !!!
a) -12x + 60 + 21 - 7x =15
-12x - 7x + 81 = 15
-19x = 15 - 81
-19x = -66
x= -66 : (-19)
x = \(\frac{66}{19}\)
Vậy x = \(\frac{66}{19}\)
b) 30x + 60 - 6x + 30 - 24x= 100
30x - 6x - 24x + 60 +30= 100
x ( 30 - 6- 24 ) + 90 = 100
x. 0 + 90 =100
x. 0 =10 ( vô lý )
\(\Rightarrow\) x \(\in\phi\)
a) => 4/3x = 7/9 - 4/9 = 1/3
=> x = 1/3 : 4/3 = 1/4
b) => 5/2 - x = 9/14 : (-4/7) = -9/8
=> x = 5/2 - (-9/8) = 5/2 + 9/8 = 29/8
c) => 3x = 2 và 2/3 - 3/4 = 8/3 - 3/4 = 23/12
=> x = 23/12 : 3 = 23/36
D) => -5/6 - x = 1/4
=> x = -5/6 - 1/4 = -13/12
a) \(\dfrac{4}{9}+\dfrac{4}{3}x=\dfrac{7}{9}\)
\(\dfrac{4}{3}x=\dfrac{7}{9}-\dfrac{4}{9}=\dfrac{1}{3}\)
\(x=\dfrac{1}{3}:\dfrac{4}{3}\)
\(x=\dfrac{1}{4}\)
b) \(\left(\dfrac{5}{2}-x\right)\left(-\dfrac{4}{7}\right)=\dfrac{9}{14}\)
\(\dfrac{5}{2}-x=\dfrac{9}{14}:\left(-\dfrac{4}{7}\right)=-\dfrac{9}{8}\)
\(x=\dfrac{5}{2}-\left(-\dfrac{9}{8}\right)\)
\(x=\dfrac{29}{8}\)
c) \(3x+\dfrac{3}{4}=2\dfrac{2}{3}\)
\(3x+\dfrac{3}{4}=\dfrac{8}{3}\)
\(3x=\dfrac{8}{3}-\dfrac{3}{4}=\dfrac{23}{12}\)
\(x=\dfrac{23}{12}:3\)
\(x=\dfrac{23}{36}\)
d) \(-\dfrac{5}{6}-x=\dfrac{7}{12}+\dfrac{-1}{3}\)
\(-\dfrac{5}{6}-x=\dfrac{1}{4}\)
\(x=-\dfrac{5}{6}-\dfrac{1}{4}\)
\(x=-\dfrac{13}{12}\)
-12(x-5)+7(3-x)=5
=> -12x+60+21-7x=5
=> -19x+81=5
=>-19x=5-81
=>-19x=-76
=>x=4
Vậy x=4
=> -12-x+3=5+7
=> 15-x=12
=> x=15-12
=> x=3
trl:
=> -12-x+3=5+7
=> 15-x=12
=>x=15-12
=>x=3
vậy x = 3
hok tốt